MODEL OF HYDRODYNAMIC MIXING OF CARBONIC POWDERS IN VACUUMATOR, USED IN STEEL-MAKING OF RUP “BMZ” - A. N. Chichko; N. V. Andrianov; S. V. Terletski; D. M. Kukuj; Ju. V. Jatskevich; O. I. Chichko (Литьë и металлургия, 2005)
The mathematical model of the mixing and dissolving process of carbonic powder in a system '"vacuumator-bowl” under influence of circulating argon is offered. The spatial distribution of hydrodynamic currents at mixing of carbonic powder, received on the basis of computer calculations is presented. The character of distribution of hydrodynamic speeds of melt (circulating currents) in industrial bowl and vacuumator for different time slots of mixing is determined.